Projet urbain et paysage littoral - Odile Jacquemin (Projets de Paysage)
The three principles of the action-thesis conducted in the littoral landscape around the Hyeres harbor (Var/France) are : the introduction of the history for the benefice of the territory project, by articulating the long history with the history of the present time, this last one constituting the evaluation ; the proposition of the entry « landscape» to build a global and shared vision ; and the conduction of touring workshops in order to cross the perspectives and develop a collective expertise. Between total history and global vision, the work of a long history associated to a fine articulation of the site and to a collective action has lead to the reevaluation of the pertinent scale of the territory project, the renewing of the sources and the enrichment of the materials and the actors of the project. The objective was to take the « landscape» out of the discourse relating to the « beauty», to develop a methodological frame renewing the local monograph in order to analyze the scale unicode2utf8(0x2018)from the local to the global». The experience offers an opportunity of appropriation adapted to the Maghreb countries as much as they share similar stakes of Mediterranean littorals.